How we developed an emergency psychiatry training course for new residents using principles of high-fidelity simulation. (October 2013) - Thomson, Alex B.; Cross, Sean; Key, Suzie; Jaye, Peter; Iversen, Amy C.
<x xml:space="preserve">Abstract</x> New psychiatry residents must rapidly acquire new clinical skills and learn to work effectively with new colleagues. In medical and surgical specialties, high-fidelity simulation with structured debriefing is widely used, but so far this has not been applied to psychiatry. We have developed a one-day simulation-based training course for emergency psychiatry which incorporates clinical and team-working skills training. Five scenarios covering key psychiatric emergencies are delivered in a purpose-built simulation facility. Patients are played by an actor or a high-fidelity manikin. Each scenario is followed by a 45-minute group debrief. Evaluation of a pilot group found that the course was well received and improved participants' workplace confidence. We are now planning to expand the course, provide it to all new residents and conduct further evaluation.